Cloud-Based IoT Systems for Disaster Management in Urban Areas - Bhadani, Rishita (Risk Assessment and Management Decisions, 2024)
The increasing trend of urbanization has made cities more vulnerable to both natural and man-made disasters. The integration of Internet of Things (IoT) technologies with cloud computing offers a powerful solution for real-time disaster monitoring, forecasting, and response in urban environments. This paper focuses on the creation and application of cloud-based IoT systems for disaster management, emphasizing their importance in improving preparedness, mitigation, and recovery efforts within urban areas. We analyze the system architecture, pinpoint essential challenges, review case studies, and consider potential future advancements.